Ukraine : Technical Assistance Report-Public Financial Management Overview. (IMF Staff Country Reports; Country Report ;, 2016)
This report has been compiled against a backdrop of political uncertainty and heightened security concerns. Public financial management (PFM) reforms may not be to the forefront of government priorities at present but severe budgetary pressures need to be addressed and measures adopted to help implement sustainable fiscal policy. The report focuses on immediate PFM reforms needs that help alleviate immediate budget pressures, and also identifies medium-term reforms to address long-standing weaknesses in PFM systems.